Towards the Accurate Thermodynamic Characterization of Enzyme Reaction Mechanisms. Issue 13 (19th May 2022) - Neves, Rui P. P.; Cunha, Ana V.; Fernandes, Pedro A.; Ramos, Maria J.
Abstract: We employed QM/MM molecular dynamics (MD) simulations to characterize the rate‐limiting step of the glycosylation reaction of pancreatic α‐amylase with combined DFT/molecular dynamics methods (PBE/def2‐SVP : AMBER). Upon careful choice of four starting active site conformations based on thorough reactivity criteria, Gibbs energy profiles were calculated with umbrella sampling simulations within a statistical convergence of 1–2 kcal ⋅ mol −1 . Nevertheless, Gibbs activation barriers and reaction energies still varied from 11.0 to 16.8 kcal ⋅ mol −1 and −6.3 to +3.8 kcal ⋅ mol −1 depending on the starting conformations, showing that despite significant state‐of‐the‐art QM/MM MD sampling (0.5 ns/profile) the result still depends on the starting structure. The results supported the one step dissociative mechanism of Asp197 glycosylation preceded by an acid‐base reaction by the Glu233, which are qualitatively similar to those from multi‐PES QM/MM studies, and thus support the use of the latter to determine enzyme reaction mechanisms. Abstract : Gibbs energy profiles were calculated with umbrella sampling simulations within a statistical convergence of 1–2 kcal ⋅ mol −1 for four starting active site conformations. The results of the QM/MM molecular dynamics (MD) simulations still depended on the starting structure, as Gibbs activation energies still varied within 5 kcal ⋅ mol −1 after 0.5 ns QM/MM MD sampling per starting conformation. The results supported the one‐step dissociative glycosylation mechanism, in agreement with single‐ and multi‐PES (potential energy surface) QM/MM studies, and support their use to study enzyme reaction mechanisms.